Road Safety Management of the Department of Public Works and Highways: Basis for Policy Recommendation - Rivera, John Philip M. (SPUP Graduate School Research Journal, 2019)
The Road Safety Audit in the Department of Public Works and Highways - Isabela First District Engineering Office is very important to address the issue of the accident potential, road accidents and most likely safety performance of the distinct plan for a road scheme, whether for new construction, or a rehabilitation of existing road and existing condition of road networks. The concept of road safety management is that all highway schemes must operate as safe as possible. This study looked into the extent of implementation of the Road Safety Management and the extent of compliance to the policies on road safety management along road networks of the Department of Public Works and Highways-Isabela First District Engineering Office. The study utilized the descriptive research design. The participants of the study consisted of forty (40) participants. The researcher made use of a questionnaire that was subjected to try-out and validation and data gathered revealed that the DPWH-Isabela First District Engineering Office complied to Department Order No. 41 Series of 2016 on the maintenance of existing signages to a moderate extent. Awareness of policies such as Department Orders for road safety is very important. The implementing rules and regulations of these Department Orders for Road Safety must be observed strictly prior for the implementation of road safety management along the national roads of the Department of Public Works and Highways. Road traffic injuries are preventable if all necessary devices are considered during the planning stage. The Implementing Rules and Regulations must be strictly enforced and these rules must be widely disseminated and observed.